Effects of bias voltage and substrate temperature on the mechanical properties and oxidation behavior of CrSiN films. (December 2021) - Chang, Li-Chun; Sung, Ming-Ching; Chen, Yung-I
Abstract: Nanocomposite CrSiN films with a Si content of 14 at.% were fabricated through reactive direct current magnetron cosputtering. The Si content was determined based on the superior mechanical properties and oxidation resistance for CrSiN films reported in a previous study. Substrate bias voltage ( V b ) and temperature ( T s ) were the process variables for sputtering CrSiN films. The results indicated that the chemical composition (Cr34–37 Si14 N49–52 ) and crystalline phase (CrN) of CrSiN films were not affected by V b or T s . The application of V b and T s significantly increased the hardness of the films from 13.4 to 22.2 GPa, and Young's modulus increased from 223 to 299 GPa. The oxidation behavior of the films annealed at 800 °C in ambient air was identical, which was accompanied by the formation of an amorphous oxide layer and extruded Cr2 O3 precipitations. Highlights: CrSiN films with 14 at.% Si exhibited a nanocrystalline CrN phase. Negative bias voltage and elevated temperature enhanced mechanical properties. The formation of an amorphous oxide layer implied the inward diffusion of O. Extruded Cr2 O3 precipitations implied the outward diffusion of Cr.